2012
DOI: 10.1007/s00436-012-2846-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, antioxidant and hepatoprotective effects of Thunbergia laurifolia Linn. on experimental opisthorchiasis

Abstract: Thunbergia laurifolia Linn (Rang Chuet) possesses antioxidant and anti-inflammatory properties as well as anticancer activities. The aim of the present study was to evaluate the efficacy of T. laurifolia in reducing inflammation from pathological changes in Syrian hamsters infected with the human liver fluke Opisthorchis viverrini. Hamster groups were also administered N-nitrosodimethylamine (NDMA) and treated with T. laurifolia. Light microscopic observation of histopathological changes, liver function tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…These results were consistent with a previous report showing that fingerroot reduced the number of inflammatory cells in hepatic tissue in hamsters subjected to O. viverrini infection and N-nitrosodimethylamine (NDMA) administration (Boonjaraspinyo et al, 2011). Similarly, a recent study (Wonkchalee et al, 2012) reported that T. laurifolia administered at 100 mg/kg/day demonstrated anti-inflammatory activity in hamsters with opisthorchiasis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results were consistent with a previous report showing that fingerroot reduced the number of inflammatory cells in hepatic tissue in hamsters subjected to O. viverrini infection and N-nitrosodimethylamine (NDMA) administration (Boonjaraspinyo et al, 2011). Similarly, a recent study (Wonkchalee et al, 2012) reported that T. laurifolia administered at 100 mg/kg/day demonstrated anti-inflammatory activity in hamsters with opisthorchiasis.…”
Section: Discussionsupporting
confidence: 89%
“…Score Month (s) post infection and groups of experiment (1) Criteria for histological grading of hepatic inflammatory activity (modified from Boonjaraspinyo et al, 2011;Wonkchalee et al, 2012;Sriraj et al, 2013). Periportal or periseptal interface hepatitis (piecemeal necrosis), 0: none, 1: mild (focal, few portal areas), 2: mild/moderate (focal, most portal areas), 3: moderate (continuous around <50% of tracts or septa), 4: severe (continuous around >50% of tracts or septa).…”
Section: Histopathological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The extract of dried leaves, dried roots, fresh leaves, and bark of T. laurifolia can be effectively used as an antidote. The antidotal activity of T. laurifolia was used against pesticides, arsenic and strychnine poisonings (Tejasen and Thongthapp, 1980), and ethanol-induced hepatotoxicity (Pramyothin et al, 2005); its anti-inflammatory use (Wonkchalee et al, 2012) has also been reported. A variety of drugs and toxic chemicals are capable of generating free radicals in the body, which may cause many diseases such as cancer, cardiovascular disease, stroke, and aging.…”
Section: Introductionmentioning
confidence: 99%
“…seeds extract against carbon tetrachloride and aflatoxin B1 might results from its potent antioxidative properties 31 . Since several detoxifying effects of T. laurifolia extracts related with antioxidant properties including hepatoprotective properties 32 , neural protection against lead poisoning 5 , and antimutagen activity 33 have been recently reported, antioxidant assays of other 'Rang Chuet' plants were performed in this study.…”
Section: Antioxidant Effects and Phenolic Content Of Plant Extractsmentioning
confidence: 99%